The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1016/j.ygeno.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

SNP markers for the genetic characterization of Mexican shrimp broodstocks

Abstract: 16Selective breeding of shrimp has major potential to enhance production traits, including growth 17 and disease resistance. Genetic characterization of broodstock populations is a key element of 18 breeding programs, as it enables decisions on inbreeding restrictions, family structure, and the 19 potential use of genomic selection. Single Nucleotide Polymorphisms (SNPs) are suitable genetic 20 markers for this purpose. A set of SNPs was developed to characterize commercial breeding 21 stocks in Mexico. Indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…With the fast growth of sequencing technologies, high-throughput genetic markers, such as single-nucleotide polymorphism (SNP), have been used in population genetics. Many studies have demonstrated that SNP arrays can improve the resolution of the differentiation of genetic stocks (Perez-Enriquez et al, 2018; Torati et al, 2019). SNP assays are a useful tool for studying population structure and the effects of natural and artificial selection at the genome scale.…”
Section: Introductionmentioning
confidence: 99%
“…With the fast growth of sequencing technologies, high-throughput genetic markers, such as single-nucleotide polymorphism (SNP), have been used in population genetics. Many studies have demonstrated that SNP arrays can improve the resolution of the differentiation of genetic stocks (Perez-Enriquez et al, 2018; Torati et al, 2019). SNP assays are a useful tool for studying population structure and the effects of natural and artificial selection at the genome scale.…”
Section: Introductionmentioning
confidence: 99%
“…Due to multiple import events and subsequent mixing of broodstocks, the genetic structure of the cultivated Mexican shrimp populations has not been well understood (Perez‐Enriquez, Robledo, Houston, & Llera‐Herrera, ). It should be noted that, in this study, besides the winter production cycle of 2014‐III, the lowest mortality was observed in 2016 (Figure ), when shrimp postlarvae were obtained from a hatchery other than the one providing the postlarvae during 2013–2015.…”
Section: Discussionmentioning
confidence: 99%
“…In northwest Mexico, approximately 20 laboratories produce 10 billion shrimp postlarvae annually through genetic improvement programmes (Mendoza-Cano et al 2014). The production laboratories of shrimp postlarvae generate fast-growth genotypes based on two-stage selection process, considering body weight and growth between 28 and 130 days of age for to increase the genetic gain for growth at harvesting age (Castillo-Ju arez et al 2010); and high-resistance genotypes with shrimp broodstock of Ecuadorian origin survivors to white spot syndrome virus to reduce mortalities caused by this virus in farmed shrimp (Perez-Enriquez et al 2018). However, genetic improvement programmes does not consider how the genotypic characterisation benefit or affect survival, growth, reproductive quality (Grijalva-Chon et al 2013) and protein requirements of the L. vannamei genotypes.…”
Section: Introductionmentioning
confidence: 99%